The main causes of soil contamination with heavy metals (Pb, Cd, Hg) on the northeastern slope of the Lesser Caucasus of the Republic of Azerbaijan - Адік Мамедов; Асадулла Абдуллаєв (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія)
Problems Statement and Purpose. The subject of discussion is soil pollution - a type of anthropogenic degradation in which the content of chemicals in soils subject to anthropogenic impact exceeds the natural regional background level. The population of the earth is growing rapidly. Population growth requires food supply and meeting their consumption. At this time, the environment is polluted. Industry and agriculture especially cause soil pollution. For this reason, its research is an urgent issue. We also analyzed environmental pollution during the study. The research area is located in the Lesser Caucasus physical-geographic region, where the most important industrial enterprises in our country are located. The region is located in the western part of Azerbaijan, in an area rich in minerals. Both non-ferrous and ferrous metals are rich here. The natural conditions are also favorable for the development of industry in the area. Its richness in mineral deposits makes large-scale research of the area relevant. Therefore, our research is dedicated to the actual topic.